Bondarchuk's War and peace : literary classic to Soviet cinematic epic - Youngblood, Denise J. (Denise Jeanne), 1952- (University Press of Kansas, 2014)
Sergei Bondarchuk's War and Peace, one of the world's greatest film epics, originated as a consequence of the Cold War. Conceived as a response to King Vidor's War and Peace, Bondarchuk's surpassed that film in every way, giving the USSR one small victory in the cultural Cold War for hearts and minds. This book, taking up Bondarchuk's masterpiece as a Cold War film, an epic, a literary adaptation, a historical drama, and a rival to Vidor's Hollywood version, recovers-and expands-a lost chapter in the cultural and political history of the twentieth century. Like many great works of literature,